Pengembangan Modul Pembelaran Materi Bilangan Pecahan Siswa di Kelas IV SDN 01 Koto Baru - Asmara, Dwi Novri; Apreasta, Lika; Pitriana, Depi (Universitas Batanghari Jambi, 2024)
This research aims to develop a learning module for learning fractions for students in class IV SDN01 Koto Baru. This research uses Research and Development (R&D). The development research model useduses ADDIE. The ADDIE model consists of 5 stages, namely Analysis, Design, Development, Implementationand Evaluation. The types of data taken from the development of this Teaching Module are qualitative andquantitative data. The data collection instruments used are Validation, Practicality sheets and Effectivenesssheets. The data collection techniques used used observation, questionnaires, documentation and tests. The dataanalysis techniques used are validation analysis, practical analysis and effectiveness analysis. Based on thedevelopment that has been carried out on the Mathematics learning module for class IV fraction material atSDN 01 Koto Baru. Then you can get the results of developing the learning module. Material mathematicsusing the ADDIE development model which can be tested in class IV at SDN 01 Koto Baru. Validation of theMathematics learning module material for class IV fractions at SDN 01 Koto Baru was assessed by threevalidators. Validation shows that the learning module obtained a percentage of 72.1% with a very validcategory. Practicality was assessed by the class teacher and four students for the learning module obtained apercentage of 89.3% with a very practical category. Effectiveness is assessed by student results. Studentlearning outcomes obtained a percentage of 82.1% in the very effective category.